Optimal taxation with current and future cohorts - Hans Fehr; Fabian Kindermann (Center for Economic Studies and ifo Institute (CESifo), 2012)
This note demonstrates that optimal tax calculations in overlapping generations models should not be based exclusively on long-run welfare changes. As the latter represent a mix of efficiency and intergenerational redistribution effects, they typically favor policies which redistribute towards future cohorts. Taking the recent study of Conesa et al. (2009) as an example, we explicitly consider short- and long-run welfare effects and isolate the aggregate efficiency consequences of a tax reform. Based on this aggregate efficiency measure, we find a much lower capital income tax rate and a significantly less progressive labor income tax schedule than Conesa et al. (2009) to be optimal. As we demonstrate, the optimality of capital income taxation is explained by the low interest elasticity of precautionary savings compared to that of life-cycle savings.
Keywords: C68; H21; D91; 330; stochastic OLG model; precautionary savings; intragenerational risk sharing and redistribution